Meningkatkan Daya Tarik Wisata Melalui Pemasaran Digital Berkelanjutan (DAWISMAPAN) di Desa Kertarahayu Bekasi - Utomo, Kurniawan Prambudi; Muhaarrom, Muhammad; Zahra, Zahra; Putri, Kesya Suciani; Maharani, Bathari (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
The Community Based Ecotourism “Kampung Kita” in Kertarahayu Village, Setu, Bekasi, faces challenges in enhancing digital marketing capacity, mainly due to limited promotional skills and inadequate access to digital media. To address these issues, this community service program applied a Sustainable Digital Marketing Strategy (DAWISMAPAN) through a participatory, needs-based training approach. The activities included identifying partner needs, developing training materials, and conducting a one-day workshop focused on social media optimization, creative visual content creation, and basic digital branding. The program results show a significant improvement in the abilities of the local Tourism Awareness Group (Pokdarwis) to promote tourism. Post-training evaluation recorded no low scores; only 4.5% of participants were at score 3, while 40.9% gave a score of 4 and 54.5% gave a score of 5. Participants successfully produced promotional content and managed social media independently, indicating a capacity increase of up to 100%. These findings confirm that targeted digital transformation through structured training strengthens community-based tourism appeal and supports the implementation of smart tourism concepts in rural areas. This program has created a relevant and sustainable model for community empowerment in tourism marketing that can be replicated in similar ecotourism destinations.